The Elusive Justice: Analyzing Disparities in Judges' Decisions on Domestic Psychic Violence Cases: Keadilan yang Sulit Dipahami: Menganalisis Disparitas Putusan Hakim dalam Kasus Kekerasan dalam Rumah Tangga - Liong, Steven; Helvis, Helvis; Markoni, Markoni; Kantikha, I Made (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to analyze the basis for judges' considerations in cases of domestic psychological violence and to examine the causes of disparities in judges' decisions. The research employed a normative juridical research method. The results showed that judges' considerations in domestic psychological violence cases were based on three factors: juridical, sociological, and ideal philosophical considerations, which resulted in different decisions. The study found that disparities in judges' decisions could not be eliminated due to various influencing factors. Nonetheless, the act of psychological violence is considered a crime that disturbs family harmony and is prohibited by Law No. 23 of 2004. This research has implications for the need to establish clear guidelines for judges in handling domestic psychological violence cases to ensure consistency and fairness in the legal system. Highlights: The judge's considerations in domestic psychological violence cases include juridical, sociological, and ideal philosophical aspects. Different considerations can result in different decisions, even in similar cases. Acts of psychological violence in the household are prohibited by Law No. 23 of 2004 and can disrupt family harmony.